DETERMINING CHILDHOOD THROUGH DNA TESTING ACCORDING TO NAHDLATUL ULAMA AND FATWA DARUL IFTA EGYPT - Lukito, Bagas; Hadi, Sutrisno; Fikri, Ikhwan (Universitas Islam Negeri Raden Fatah Palembang, 2025)
Nasab is one of the most important things in Islam, as it relates to one's rights and obligations in life. With the development of increasingly modern technology, DNA (Deoxyribo Nucleic Acid) tests can now be used as a tool to scientifically determine a child's nasab. The research method used is library research with a qualitative approach. Primary data was obtained from the decision of the XXXI Nahdlatul Ulama Congress and the fatwa of Darul Ifta Egypt, while secondary data was obtained from other sources relevant to the topic of this research, such as books, journals, and articles. The results showed that Nahdlatul Ulama through its decision; can deny ilhaq al-Nasab, but not necessarily be able to determine ilhaq al-Nasab, Meanwhile, Darul Ifta Egypt in its fatwa stated that the use of DNA tests allows for the determination of the child's lineage to be accepted in Islam in certain situations where there is no other way to establish lineage with sufficient confidence. DNA testing should be used as an objective and scientific tool to confirm family relationships with prudence, in establishing lineage as a solution when it is impossible or difficult to establish lineage by traditional or conventional means. This research is expected to contribute to understanding the views of Nahdlatul Ulama and Darul Ifta Egypt regarding the determination of children's nasab through DNA testing, and can be a reference for further research related to this topic. Keywords: Nasab; DNA; NU; Fatwa Darul Ifta.